Cardiopulmonary Resuscitation Training and Its Impact on Health Care Students' Knowledge and Anxiety Levels - Duzcu, Tuğba; Özel, Yasemin; Hasgül, Ergün (IPR Journals and Books (International Peer Reviewed Journals and Books), 2024)
Purpose: This study examines the impact of cardiopulmonary resuscitation (CPR) training on the knowledge and anxiety levels of healthcare students in the Home Patient Care Program. Cardiac arrest, a life-threatening condition requiring immediate intervention, underscores the critical importance of proper CPR application. Methodology: The research utilized an experimental design with pre-test and post-test evaluations, involving 77 first-year students from Kastamonu University's Tosya Vocational School of Health Services. Participants were divided into experimental (n=34) and control (n=43) groups. The experimental group received five weeks of CPR and stress-anxiety management training based on the European Resuscitation Council's 2015 guidelines. Data were collected using a CPR knowledge questionnaire and the State-Trait Anxiety Inventory (STAI). Findings: Results revealed significant improvements in the CPR knowledge scores of the experimental group, increasing from 3.47 (±1.73) to 10.09 (±1.68) (p < 0.001). Concurrently, their state anxiety levels decreased from 45.09 (±10.54) to 38.50 (±9.08) (p < 0.001), and trait anxiety scores showed a moderate reduction. No significant changes were observed in the control group. Unique Contribution to Theory, Practice and Policy: The findings highlight the necessity of integrating CPR training with stress and anxiety management programs in healthcare education. Such training enhances students' ability to perform CPR effectively and reduces psychological barriers, ultimately improving patient outcomes. Further research with broader samples is recommended to validate these results.